Penggunaan Metode Diskusi Kelompok Untuk Memahami Jurnal Kesehatan Ditinjau Dari Ranah Kognitif Pada Mahasiswa Jurusan Fisioterapi - Noerdjanah Noerdjanah; Jasmine Kartiko Pertiwi (Interest : Jurnal Ilmu Kesehatan, 2018)
Abstract : Cognitive Domain, Health Journal, Group Discussion. It is very important for physiotherapist to understand Journal and to know the development of theory and practice. Physiotherapist Learning process is based on evidence based so that they must understand the content of journal. Most students don’t understand the content of journal. One of learning method that can used for understanding of journal is group discussion. This study is interested in the class research action which the title is Using Group Discussion Method for understanding Health Journal from cognitive domain to Physiotherapy student of Health Polytechnic of Surakarta. Research Objective is to recognize the achievement of ability to understand the content of journal in cognitive domain of English Lesson in group discussion of Physiotherapy student of Health Polytechnic of Surakarta. The construction of research that be used by the class research action (PTK), Subject are 65 student in eight groups. The research is hoped to be benefit for researcher and can be used as basic reference of research deeply.